2010
DOI: 10.3109/08990220903471765
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood lactate is associated with increased motor cortex excitability

Abstract: No information has yet been provided about the influence of blood lactate levels on the excitability of the cerebral cortex, in particular, of the motor cortex. The aim of the present study was to examine the effects of high blood lactate levels, induced with a maximal cycling or with an intravenous infusion, on motor cortex excitability. The study was carried out on 17 male athletes; all the subjects performed a maximal cycling test on a mechanically braked cycloergometer, whereas 6 of them were submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 42 publications
1
43
0
2
Order By: Relevance
“…We have recently observed in adult male athletes (Coco et al 2010) that, after an acute exhaustive exercise, there is a strong increase of blood lactate associated with a significant decrease of the MT, that is, an increase of blood lactate is associated with an enhancement of the motor cortex excitability evaluated with TMS. However, since during a strenuous physical performance several variables will change besides increased lactate, as systemic hormones, cytokines, increased levels of adrenergic hormones both peripherally and centrally (cf., Gleeson 2007), we analyzed the effects on cortical excitability of an intravenous infusion of lactate, in subjects not performing any exercises.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We have recently observed in adult male athletes (Coco et al 2010) that, after an acute exhaustive exercise, there is a strong increase of blood lactate associated with a significant decrease of the MT, that is, an increase of blood lactate is associated with an enhancement of the motor cortex excitability evaluated with TMS. However, since during a strenuous physical performance several variables will change besides increased lactate, as systemic hormones, cytokines, increased levels of adrenergic hormones both peripherally and centrally (cf., Gleeson 2007), we analyzed the effects on cortical excitability of an intravenous infusion of lactate, in subjects not performing any exercises.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, lactate may delay the onset of fatigue by maintaining the excitability of muscle and that this situation may occur during extremely intensive exercise (Philp et al 2005). We suggested (Coco et al 2010) that also in the motor cortex the lactate could carry out a protective role against fatigue. On the basis of the present result we may conclude that women appear to be more protected by lactate against ''central fatigue''.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, if on the one hand an increase of blood lactate is associated with an improvement in the excitability of the primary motor cortex [12,19,20], on the other hand it is concomitant to a worsening of attentional capabilities involving the prefrontal cortex [1,21,22]. Furthermore, experiment carried out with visual- [9] and somatosensory-evoked potentials [23] has shown that increases of blood lactate are associated, in both cases, with an improvement in the conduction time between the periphery and the primary sensory areas and a worsening of intracortical communication between primary areas and adjacent regions.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is the energetic metabolite used to sustain glutamatergic synaptic activity, in particular in pathological conditions that alter energy production, such as hypoglycemia or anoxia/ischemia (Rouach et al 2008). However, it has recently been observed that an increase of blood lactate is associated with a worsening of attentional processes mediated by prefrontal cortex (Coco et al 2009) and with an improvement of excitability of primary motor cortex (Coco et al 2010). There is no information, to our knowledge, about the possible effects of blood lactate increases, such as those evoked by exhaustive exercise, on excitability of spinal -motoneurons.…”
Section: Introductionmentioning
confidence: 97%